2005
DOI: 10.1002/micr.20093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HTK on the microcirculation in the rat cremaster muscle during warm ischemia and reperfusion

Abstract: Histidine-tryptophan-ketoglutarate (HTK) preserves rat muscle function during cold storage. We examined the effect of HTK perfusion on preservation of microvascular function during 4 h of warm ischemia and subsequent reperfusion (I/R) in the rat cremaster muscle. Leukocyte-endothelium interactions, capillary perfusion, and arteriole diameters were quantified prior to HTK-perfusion and/or ischemia, and at 0, 1, and 2 h after restoration of blood flow. In all groups, the number of rolling leukocytes increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 31 publications
1
18
1
Order By: Relevance
“…For antioxidants to become effective, the reperfusion period should include a reflow period, in which oxygen enters the tissue and free radicals are formed. In the present study, as well as in a previous study [6], we demonstrated that, after a period of 4 h of total normothermic ischemia, capillary perfusion resumed at 50% of preischemic baseline levels right at the start of reperfusion. Within the subsequent 2 h reperfusion period this parameter recovered almost completely to baseline levels.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…For antioxidants to become effective, the reperfusion period should include a reflow period, in which oxygen enters the tissue and free radicals are formed. In the present study, as well as in a previous study [6], we demonstrated that, after a period of 4 h of total normothermic ischemia, capillary perfusion resumed at 50% of preischemic baseline levels right at the start of reperfusion. Within the subsequent 2 h reperfusion period this parameter recovered almost completely to baseline levels.…”
Section: Discussionsupporting
confidence: 65%
“…Previously, we studied the effects of 10 min of preischemic perfusion with HTK on the microvascular consequences of 4 and 6 h of ischemia [6]. HTK did not influence the (transient) decrease in tissue perfusion observed after ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations